A hybrid piezo-dielectric wind energy harvester for high-performance vortex-induced vibration energy harvesting. (March 2021) - Lai, Zhihui; Wang, Shuaibo; Zhu, Likuan; Zhang, Guoqing; Wang, Junlei; Yang, Kai; Yurchenko, Daniil
Highlights: A hybrid piezo-dielectric system can harvest vortex-induced vibrational energy. Structural and aerodynamic parameters are identified from wind tunnel experiments. The system can operate effectively within a low wind speed range. More power can be harvester from the VI DEG than the PZT in the lock-in region. Smaller mass, higher stiffness and larger bluff body diameter are beneficial designs. Abstract: This paper proposes a novel hybrid piezo-dielectric (PD) wind energy harvester, to efficiently harvest the vortex-induced vibration (VIV) energy from low-speed wind. The hybrid PD harvester brings together the following two electromechanical transduction mechanisms: piezoelectric ceramic (PZT) sheets and a vibro-impact (VI) dielectric elastomer generator (DEG). The PZT sheets directly transduce the beam's vibration into electricity, whereas the VI DEG transduces the impacts between the inner ball and the dielectric elastomer membranes resulting from the bluff body's vibration into electricity. The theoretical model of the hybrid PD harvester subjected to VIV is formulated. Wind tunnel experiments are performed to validate the aerodynamic part of the theoretical model and identify the aerodynamic coefficients. Afterward, based on the theoretical model, the numerical investigation of the hybrid PD harvester is conducted, which uncovers the insights of the conjunction of the PZT and VI DEG for VIV energy harvesting enhancement. It is seen that in the lock-in region of the VIV, where both the PZT and VI DEG can effectively harvest the VIV energy, the VI DEG can generate much higher power. This demonstrates the superiority of the hybrid PD harvester. Parametrical studies show that the smaller mass, higher stiffness and larger diameter of the bluff body are beneficial designs, which broadens the working wind range and enhances the generate power.